METHODS FOR DIAGNOSING THE FORMATION OF RETENTION OF THE UPPER PERMANENT CANINES - Olimov S. Sh; Bakaev Zh. N (International Engineering Journal For Research & Development, 2021)
This article makes analyses of the methods for diagnosing the formation of retention of the upper permanent canines. On this case, research has pointed out on the development of the research on different points as the whole. In conlcusion, research has been pointed on various features of the methodology and theoritical points as the whole.